The Effects of Game-Based Learning on Vocabulary Acquisition in B1 Level Learners - Sodiqova Gavharoy (Western European Studies, 2024)
This research investigates the impact of game-based learning (GBL) on vocabulary development in B1 level students. We evaluated vocabulary acquisition before and after GBL interventions using a combination of quantitative and qualitative methods, as well as gathering information on learner experiences. Our results suggest that B1 level students who participated in GBL experienced notable enhancements in vocabulary retention and usage. Furthermore, students also mentioned a rise in their levels of motivation and enjoyment while engaging in game-based learning activities. These findings indicate that including GBL in language learning programs may be a beneficial strategy for improving vocabulary proficiency in B1 level students.
Keywords: Game-Based Learning; vocabulary growth; strategy